Comparative CFD modeling of foam and conventional pellet catalysts in glycerol steam reforming - Simasatitkul, Lida; Phitchayakorn, Chattharika; Amornraksa, Suksun; Anantpinijwatna, Amata; Assabumrungrat, Suttichai (My University, 2025)
A novel approach to glycerol valorization via steam reforming was investigated through computational fluid dynamics (CFD) modelling. The performance characteristics of conventional pellet catalysts were compared with foam catalysts in a 6-inch diameter packed bed reactor. A two-dimensional pseudo-homogeneous steady-state model was employed to evaluate catalyst configurations ranging from 10 to 30 pores per inch (PPI). The foam catalyst structures exhibited superior performance across key metrics, achieving maximum hydrogen yield (60 %) at one-third of the reactor length whilst reducing pressure drop by 95 % compared to conventional pellets. Within the foam configurations, the 10PPI variant demonstrated optimal performance characteristics, with an 80 % reduction in normalized pressure drop compared to 30PPI, whilst maintaining comparable product yields. The enhanced performance was attributed to the open-cell architecture, which facilitated improved mass transfer and reduced diffusion limitations. These findings suggest that foam catalysts represent a promising alternative to conventional pellet configurations for glycerol steam reforming processes.
Keywords: Catalyst structures; Computational fluid dynamics (CFD); Foam catalysts; Glycerol steam reforming; Hydrogen production